Super-weather-resistant and high-gloss titanium dioxide and preparation method thereof
Through the use of high -amount zinc salt and a small amount of aluminum salt during the preparation process of titanium pink, and combined with silicon and aluminum envelope technology, the lack of high weather resistance and high gloss of titanium pink powder in existing technologies can be solved. The effect of ultra -weather resistance and high luster.
Patent Information
- Application Number
- CN202411488540.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, high weather resistance titanium dioxide cannot meet the demand in some cases, especially when high gloss and super weather resistance are required.
Using a method that combines a high amount of zinc salt with a small amount of aluminum salt, the metatitanic acid is treated with salt to fill the lattice defects of TiO2, and the multi-layer coating technology of silicon coating and aluminum coating is used to improve the performance of titanium dioxide. Weather resistance and gloss.
The ultra -weather and high luster of titanium pink powder is realized, it improves its stability and optical properties in acidic environments, and meets the needs of high weather resistance and high gloss.
Smart Images

Figure BDA0005099353820000061 
Figure BDA0005099353820000071 
Figure BDA0005099353820000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of titanium dioxide, and in particular to a super-weather-resistant and high-gloss titanium dioxide and a preparation method thereof. Background Art
[0002] Titanium dioxide, scientifically known as titanium dioxide (TiO2), is a white inorganic pigment with the characteristics of non-toxicity, excellent opacity, whiteness and brightness. It is considered to be the best and most important white pigment in the world. Titanium dioxide accounts for more than 80% of the total white pigment usage and is widely used in coatings, plastics, papermaking, printing inks, chemical fibers, rubber and cosmetics. Due to some inherent defects of titanium dioxide powder (such as photochemical activity), it is necessary to coat the titanium dioxide particles with substances that do not have luminescent catalytic effects, such as hydrated oxides of SiO2 and Al2O3, so that the titanium dioxide particles do not directly contact the organic medium in the carrier, and provide a position for recombination with the hydroxyl polar groups to prevent destructive reactions.
[0003] The Chinese patent with the publication number CN112143261A discloses a method for preparing anatase titanium dioxide with high weather resistance. The method comprises the following steps: inorganic coating is performed on the titanic acid after the filter cake is slurried after the second washing, and the slurry after the inorganic coating is washed and calcined to obtain a crude titanium dioxide product. The crude titanium dioxide product is ground by a roller mill, and the ground titanium dioxide is organically coated by an air flow pulverization process to obtain a highly weather resistant anatase titanium dioxide. The method for preparing anatase titanium dioxide with high weather resistance in this scheme performs inorganic coating before the crude product is prepared, thereby eliminating some processes for the finished titanium dioxide product. The advantages are: the filter cake after the second washing is slurried, dispersed with phosphoric acid, and then coated with silicon. In this process, sodium silicate is added for coating and calcined. Silicon dioxide can enter the photoactive sites during the high-temperature calcination process, greatly improving the weather resistance of titanium dioxide. Dilute phosphoric acid first plays a dispersing role, and can also act as a rutile inhibitor during calcination, reducing the conversion of titanium dioxide to rutile; potassium hydroxide adjusts the pH to ensure that the pH is neutral before sodium silicate is added.
[0004] The Chinese patent with the publication number CN106118140B discloses a method for preparing a high-whiteness and high-temperature-resistant masterbatch titanium dioxide. The rutile masterbatch titanium dioxide is based on a sulfuric acid production process. After being fully bleached, washed with water and treated with salt, it is calcined to prepare a rutile base material that has not been surface-treated and has good whiteness and particle fineness. After being fully crushed by wet sand milling, it is inorganically coated and flash dried. During air flow crushing, it is treated with organic coating to prepare a masterbatch titanium dioxide with low moisture absorption, fine particle size, high whiteness and high temperature resistance. The salt treatment step is to carry out combined salt treatment with zinc salt, potassium salt and phosphate salt. The amount of phosphate salt added is 0.4% of the mass of TiO2 based on the mass of P2O5; the amount of zinc salt added is 0.05-0.2% of the mass of TiO2 based on the mass of ZnO; and the amount of potassium salt added is 0.25-0.45% of the mass of TiO2 based on the mass of K2O. Potassium salt can make the particles loose after calcination and adjust the rutile crystal form. Zinc salt can inhibit the rapid transformation of the particle crystal form, which is beneficial to the slow and uniform growth of particles during the crystal transformation process, thereby improving the particle size distribution and smoothing the particle morphology.
[0005] However, for some occasions requiring titanium dioxide with higher weather resistance, the products in the above two prior arts often cannot meet the requirements. Summary of the invention
[0006] The purpose of the present invention is to solve the deficiencies of the prior art and provide a super weather-resistant, high-gloss titanium dioxide and a preparation method thereof to meet the demand for super weather-resistant, high-gloss titanium dioxide.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing super weather-resistant and high-gloss titanium dioxide comprises the following steps:
[0009] S1, taking metatitanic acid and adding deionized water to make a slurry to obtain a metatitanic acid slurry, adding a salt treatment agent for reaction, wherein the salt treatment agent includes potassium salt, phosphorus salt, zinc salt and aluminum salt, wherein the amount of phosphorus salt added is 0.01-0.15% of the mass of TiO2 based on the mass of P2O5; the amount of zinc salt added is 5-10% of the mass of TiO2; the amount of potassium salt added is 0.25-0.45% of the mass of TiO2; and the amount of aluminum salt added is 0.05-0.2% of the mass of TiO2 based on the mass of Al2O3;
[0010] S2, filtering, drying and calcining the slurry obtained in S1 to prepare a primary rutile titanium dioxide product;
[0011] S3, crushing, pulping and sand-milling the primary rutile titanium dioxide obtained in S2;
[0012] S4, making the surface of the titanium dioxide particles in the slurry prepared in S3 uniformly coated with hydrated SiO2;
[0013] S5, making the surface of the slurry particles obtained in S4 evenly coated with a dense aluminum film, washing and drying;
[0014] S6, calcining, cooling and crushing the material dried in S5.
[0015] S1 is to add excess zinc salt to the titanate treatment agent to fill the lattice defects of TiO2, prevent the diffusion of voids, promote the recombination of particles, and achieve the effect of inhibiting photocatalytic reaction. Titanium liquid is hydrolyzed to prepare titanic acid. Due to the strong particle bonding effect in titanic acid, high water and sulfate content, its pores are numerous, long, and uneven. After calcination, the growth of grains and the compact lattice of titanic acid lead to the collapse of the pores. The water and sulfate supporting the pores also cause the collapse of the pores after they are released, which is the lattice defect. Adding a large amount of salt treatment agent zinc and aluminum salt can fill the lattice defects and stabilize the lattice. In the traditional rutile titanium dioxide production, phosphoric acid or phosphate, potassium salt, zinc salt is used as the salt treatment agent during the titanate treatment. Usually, the amount of ZnO added is generally 0.1-0.3%, the amount of KOH added is 0.25-0.5%, and the amount of H3PO4 added is 0.01-0.15%. Such a combination can basically meet the pigment indicators and application performance requirements of general-grade products. However, in some occasions where titanium dioxide with higher weather resistance is required, such products often cannot meet the requirements. In recent years, many companies have launched products treated with aluminum salts to improve weather resistance, but aluminum salt is a negative catalyst. Aluminum salt-treated products often require higher calcination temperatures, and their production process consumes relatively high energy. In addition, the color index and product softness of aluminum salt-treated products are not as good as those treated with zinc salts. The present invention adopts a method combining a high amount of zinc salt and a small amount of aluminum salt to improve its defects and overcome the above-mentioned shortcomings. It is emphasized that the titanium dioxide prepared by the present invention has better weather resistance to acid.
[0016] According to the embodiments of the present invention, the present invention can be further optimized. The following is the technical solution formed after optimization:
[0017] In S3, the primary rutile titanium dioxide is made into a slurry with a concentration of 700-800 g / L, and sodium hexametaphosphate is added in an amount of 0.2-0.4% by mass of TiO2 based on the mass of P2O5, or sodium silicate is added in an amount of 0.2-0.4% by mass of TiO2 based on the mass of SiO2, and then sand-milled.
[0018] In one preferred embodiment, S4 includes the following steps: preparing the sand-grinding slurry obtained in S3 into a slurry with a concentration of 200-400 g / L, heating it to 75-95°C, adding sodium silicate with a TiO2 mass of 2-3% in terms of SiO2, controlling the slurry pH to 9.5-10.5 and stirring, adding acidulant acetic acid until the slurry pH reaches 3.0-4.0, and maturing; preferably, the acidulant is acetic acid or dilute sulfuric acid; further preferably, the acidulant is acetic acid.
[0019] The particles obtained by calcining untreated titanium dioxide are very small, have a high specific surface energy and are extremely unstable. They quickly agglomerate at high temperatures to form metastable larger powders. The smaller the TiO2 particles, the stronger the interaction between the particles, and the easier it is to agglomerate. There are lattice defects on the surface of pure TiO2, and there are many photo-activated points. Under the action of ultraviolet rays, chemical reactions will occur, causing the pigment to change color. The smaller the particles, the more activated points, and the worse the light resistance and weather resistance. In order to improve weather resistance and chemical stability, its surface must be treated and coated with a film to block the activation points.
[0020] Silicon coating is divided into dense film and porous film. Dense film has particularly good weather resistance and is often used in high gloss, high weather resistance and coatings such as enamel and plastic. The commonly used coating agents for silicon coating are sodium silicate, silicon halogen compounds, silicon acetate or some organic silicon compounds such as Si(OCH3)4, Si(NH2)4, Si(NH4)4, Si(OC2H5)4, etc., which are hydrolyzed to form Si(OH)4, SiO(OH)2, SiO2.XH2O and finally form a polymer of silicon hydroxide.
[0021] Through step S4, the hydrated SiO2 is evenly coated on the surface of the titanium dioxide particles throughout the entire process.
[0022] S4 dense silica coating, silicate polymerization initially forms silicate sol, the surface energy of sol is extremely large, and it is constantly moving in the solution. Subsols collide with each other or with titanium dioxide particles to condense and grow, sols collide with each other to form their own nuclei, and sols collide with titanium dioxide particles to form films on the surface of titanium dioxide particles, forming the following three situations under different conditions. (1) The acid concentration at a certain point in the slurry is not high, and the silicate sol formed is evenly distributed in the solution at a lower concentration. At this time, the surface area of titanium dioxide particles is relatively large, and the probability of silicate sol colliding with them is much greater than the probability of silicate sol colliding with each other, which is conducive to obtaining a uniform and dense coating on the surface of titanium dioxide particles. (2) When the acidity is very high, the concentration of the polymerized silicate sol formed by silicate is high. At this time, the probability of sol colliding with titanium dioxide particles and sol colliding with each other is relatively high, so that homogeneous nucleation and heterogeneous nucleation occur simultaneously. The higher the sol concentration, the greater the probability of homogeneous nucleation, and the greater the proportion of homogeneous nucleation products in the coated product. (3) When the acidity in a certain area of the slurry is too high, a large amount of sol is generated locally in the slurry, and homogeneous nucleation and heterogeneous nucleation are concentrated in this local area, resulting in poor coating quality. Use acetic acid or dilute sulfuric acid as an acidifier to slowly release H ions. This avoids the occurrence of homogeneous nucleation, allowing the silicon to be coated on the surface of the titanium dioxide particles at a slow speed throughout the process. Mature for 1-2 hours.
[0023] In one preferred embodiment, S5 includes the following steps: cooling the slurry obtained in S4 to 55-65°C, adjusting the pH value to 4.5-5.5, adding aluminum sulfate or sodium aluminate with a TiO2 mass of 2-5% based on Al2O3 to coat the dense aluminum, and aging for 1.5-2 hours.
[0024] When the pH value of S5 is 4.5-5.5, the aluminum coating on the surface of titanium dioxide is relatively smooth and compact. This is because the nano-amorphous hydrated aluminum oxide crystal nuclei agglomerate and grow to form a dense coating layer.
[0025] In one preferred embodiment, the method for preparing super weather-resistant and high-gloss titanium dioxide further comprises S7, adding water to the titanium dioxide obtained in S6 to prepare a titanium dioxide slurry with a mass concentration of 200 to 400 g / L, adding aluminum sulfate or sodium aluminate with a TiO2 mass of 0.1 to 1% based on Al2O3, controlling the pH value to 8 to 9, and obtaining a boehmite-type aluminum coating;
[0026] S8: washing, drying, adding all-purpose powder and steam powder to the coating material prepared in S7.
[0027] The boehmite-type hydrated alumina precipitated by S7 at a pH value of 8-9 is loose and flocculent. When this form of alumina is coated on the surface of TiO2 particles, it is beneficial to improve the dispersibility of titanium dioxide particles.
[0028] After calcining titanium dioxide, the weather resistance of titanium dioxide is improved, but the whiteness and gloss of titanium dioxide are affected. It is necessary to take the coating method to further improve the whiteness and optical properties of titanium dioxide, weather resistance and gloss. At the same time, after a small amount of aluminum coating, the surface of titanium dioxide particles is wrapped by a low-bound water film layer, which weakens the interaction between titanium dioxide particles. A small amount of energy is required to achieve excellent particle size and particle size distribution, and it has good formula applicability.
[0029] In one preferred embodiment, the drying temperature in S2 is 150-200°C, and the calcination temperature is 820-870°C.
[0030] In a preferred embodiment, the addition time of acetic acid in S4 is 1.5 to 3 hours.
[0031] In one preferred embodiment, the aging time in S4 is 1 to 2 hours. This aging time can make the hydrated SiO2
[0032] The surface of titanium dioxide particles is evenly coated throughout the whole process.
[0033] In one preferred embodiment, the calcination temperature in S6 is 600-800° C., and the calcination time is 10-30 minutes.
[0034] Preferably, the calcination temperature of S6 is 700-800°C, and the coated titanium dioxide is calcined at this temperature range for 20-30 minutes to dehydrate the hydrated SiO2 and hydrated Al2O3 of the coating to form a denser film layer, further reduce the surface hydroxyl content, reduce the surface voids of the titanium dioxide, and improve the weather resistance of the titanium dioxide.
[0035] The invention also discloses titanium dioxide prepared according to the preparation method.
[0036] Preferably, the concentration of the metatitanic acid slurry in S1 is 250-350 g / L.
[0037] Preferably, the titanate slurry in S1 is prepared by washing qualified titanate with water and then adding deionized water to make a slurry.
[0038] Preferably, the rotation speed of the sand mill in S3 is 8000-10000 rpm, and the sand milling is performed for 1-2 hours.
[0039] Preferably, the stirring time in S4 is 30 to 60 minutes.
[0040] The key point of the present invention is that after the coated product is calcined twice, the hydrated SiO2 and hydrated Al2O3 of the coated product are dehydrated to form a denser film layer, further reducing the hydroxyl content on the surface of TiO2, giving the titanium dioxide super weather resistance. It can be seen from the acid solubility, see attached table 1-2. The lower the acid solubility of titanium dioxide, the better its weather resistance.
[0041] The comparative document CN106118140 B has a calcination temperature of 950-980°C after the metatitanic acid is treated with salt, and a primary titanium dioxide powder with a rutile conversion rate of 94-98% is prepared. The metatitanic acid of the present invention has a calcination temperature of 820-870°C after the metatitanic acid is treated with salt, and a primary titanium dioxide powder with a rutile conversion rate of more than 99.5% is prepared. The present invention has a low calcination temperature and low energy consumption.
[0042] The invention product of patent CN 105118140B has a rutile conversion rate of only 94-98%. The product has a high content of anatase titanium dioxide and belongs to mixed crystal titanium dioxide. The weather resistance of mixed crystal titanium dioxide is inherently poor. The invention has a rutile content of more than 99.5% for titanium dioxide and has super weather resistance after secondary calcination.
[0043] The invention of patent CN112143261A is anatase titanium dioxide, while the present invention is rutile titanium dioxide. Compared with anatase titanium dioxide, rutile titanium dioxide has a smaller and more compact unit lattice and higher stability. Anatase titanium dioxide will be converted into rutile titanium dioxide at high temperature. Therefore, the weather resistance of anatase titanium dioxide is worse than that of rutile titanium dioxide.
[0044] The beneficial effects of the present invention are:
[0045] (1) When treating with metatitanate, an excess of zinc salt is added to fill the lattice defects of TiO2, prevent the diffusion of voids, promote the recombination of particles, and achieve the effect of inhibiting the photocatalytic reaction. The present invention adopts a method of combining a high amount of zinc salt with a small amount of aluminum salt to improve the color index and product softness.
[0046] (2) Silica coating uses acetic acid as an acidifier, which can slowly release H + ions, so that silicon (SiO2) is evenly coated on the surface of titanium dioxide particles at a slow speed throughout the whole process.
[0047] (3) After coating, calcination is performed to dehydrate the hydrated SiO2 and hydrated Al2O3 in the coating to form a denser film layer, further reducing the surface hydroxyl content and the surface voids of the titanium dioxide. The titanium dioxide prepared by the method of the present invention can achieve a high film coverage rate, and on the premise of ensuring the gloss of the product, give the titanium dioxide super weather resistance.
[0048] (4) After coating, titanium dioxide is calcined and then coated for the second time to ensure the whiteness and glossiness of titanium dioxide. DETAILED DESCRIPTION
[0049] Example 1
[0050] (1) Take a second wash material with a concentration of 300 g / L of metatitanic acid (calculated as TiO2) and a volume of 300 mL in a glass beaker, start stirring, add 2.25 g of 10% KOH (the amount of potassium salt added is 0.25% of the mass of TiO2), and stir for 30 minutes; add 1.35 g of phosphoric acid with a weight concentration (calculated as P2O5) of 10% (the amount of phosphorus salt added is 0.15% of the mass of TiO2 based on the mass of P2O5), and stir for 30 minutes; add 9.0 g of zinc oxide powder (the amount of zinc salt added is 10% of the mass of TiO2); stir for 30 minutes, add 1.79 mL of aluminum sulfate (calculated as Al2O3) with a concentration of 100.51 g / L (the amount of aluminum salt added is 0.20% of the mass of TiO2 based on the mass of Al2O3), and stir for 1 hour.
[0051] (2) The treated slurry is filtered to form a filter cake, which is placed in an evaporating dish and dried at 150°C. The dried material is broken into pieces in the evaporating dish and calcined in a muffle furnace at 850°C for 1 hour. The rutile crystal content of the calcined sample is detected to be 99.6%. The color index of the sample is: L*: 98.78b*: 1.35.
[0052] (3) Take 80 g of the calcined sample, crush it with a universal grinder, add deionized water to make a slurry with a slurry concentration of 700 g / L, add 4 g of sodium hexametaphosphate with a weight concentration of 5% (based on the mass of P2O5) (the amount of sodium hexametaphosphate added is 0.25% of the mass of TiO2 based on the mass of P2O5), and sand grind at 9600 rpm for 1 hour.
[0053] (4) Prepare the sand-grinded slurry to a concentration of 300 g / L, raise the temperature to 95°C, add 13.3 g of sodium silicate solution (sodium silicate with a weight percentage of 2.0% of SiO2 and TiO2 mass) with a concentration of 12% (in terms of SiO2) through an axial flow pump, and add it over 30 minutes. Use NaOH solution to control the pH of the slurry to 10.0, and stir for 30 minutes. Add acidulant acetic acid through an axial flow pump at about 90 minutes until the pH value reaches 3.0, and the aging time is 1 hour.
[0054] (5) Cool the slurry to 60°C, add NaOH solution dropwise to make the pH value of the slurry 5.5, and add 23.9mL of aluminum sulfate (aluminum sulfate with a concentration of 100.51g / L, 3% by mass of TiO2 in terms of Al2O3) and NaOH solution in parallel, and control the pH value to 4.5-5.5. The addition time is 55 minutes. Mature for 1.5 hours. Wash with water and dry. The acid solubility of the sample is 8.5%; the color index of the sample is L*: 98.82b*: 1.31, and the application performance is tested. The gloss at 20° is 68, and the gloss at 60° is 80.
[0055] (6) The dried material was placed in a muffle furnace and calcined at 600°C for 30 minutes, cooled, and universally crushed. The acid bath rate of the test sample was 3.96%, and the color index of the test sample was: L*: 98.55b*: 1.65. The application performance was tested. The gloss at 20° was 62, and the gloss at 60° was 75.
[0056] (7) Titanium dioxide is added with water to prepare a titanium dioxide slurry with a concentration of 300 g / L, and 0.5% aluminum sulfate (calculated as Al2O3) and NaOH solution are added to control the pH value to 9 for coating.
[0057] (8) Wash the coating material with water, dry it, crush it with universal powder, and steam powder. The acid solubility of the sample is 3.81%, and the color index of the sample is: L*: 98.82b*: 1.30. The application performance is tested. The gloss at 20° is 68, and the gloss at 60° is 80.
[0058] Table 1 Performance test results of titanium dioxide obtained in Example 1
[0059]
[0060] Example 2
[0061] (1) Take a second wash material with a concentration of 300 g / L of titanic acid (calculated as TiO2) and a volume of 300 mL in a glass beaker, start stirring, add 4.5 g of 10% KOH by weight, and stir for 30 minutes; add 0.09 g of 10% phosphoric acid by weight (calculated as P2O5), and stir for 30 minutes; add 4.5 g of zinc oxide powder; stir for 30 minutes, add 0.45 mL of aluminum sulfate (calculated as Al2O3) with a concentration of 100.51 g / L, and stir for 1 hour.
[0062] (2) The treated slurry is filtered to form a filter cake, which is placed in an evaporating dish and dried at 150°C. The dried material is broken into pieces in the evaporating dish and calcined in a muffle furnace at 850°C for 1 hour. The rutile crystal content of the calcined sample is detected to be 99.5%. The color index of the sample is: L*: 98.76b*: 1.38.
[0063] (3) Take 80 g of the calcined primary sample, crush it with a universal grinder, add deionized water to make a slurry with a slurry concentration of 700 g / L, add 4 g of sodium hexametaphosphate with a weight concentration of 5% (calculated as P2O5), and sand grind at 9600 rpm for 1 hour.
[0064] (4) Prepare the sand-grinded slurry to a concentration of 300 g / L, raise the temperature to 90°C, add 13.3 g of sodium silicate solution with a weight percentage concentration of 12% (in terms of SiO2) through an axial flow pump, and add for 30 minutes. Use NaOH solution to control the pH of the slurry to 10.0, and stir for 30 minutes. Add acidulant acetic acid through an axial flow pump at about 90 minutes until the pH value is 4.0, and the aging time is 1 hour.
[0065] (5) Cool the slurry to 65°C, add NaOH solution dropwise to make the slurry pH value 4.5, and add 23.9mL of aluminum sulfate with a concentration of 100.51g / L and NaOH solution in parallel, and control the pH value to 4.5-5.5. The addition time is 55 minutes. Ripen for 1.5 hours, wash with water, and dry. The acid solubility of the sample is 9.1%; the color index of the sample is: L*: 98.80b*: 1.33, and the application performance is tested. The gloss at 20° is 67, and the gloss at 60° is 80.
[0066] (6) The dried material was placed in a muffle furnace and calcined at 800°C for 10 minutes, cooled and universally crushed. The acid bath rate of the sample was tested to be 3.56%, and the color index of the sample was tested to be: L*:98.50b*:1.65. The application performance was tested to be 60 at 20° gloss and 70 at 60° gloss. (7) Titanium dioxide was added with water to prepare a titanium dioxide slurry with a concentration of 300 g / L, and 0.5% aluminum sulfate (in terms of Al2O3) and NaOH solution were added to control the pH value to 9 for coating.
[0067] (8) Wash the coating material with water, dry it, crush it with universal powder, and steam powder. The acid solubility of the sample is 3.23%, and the color index of the sample is: L*: 98.82b*: 1.33. The application performance is tested. The gloss at 20° is 68, and the gloss at 60° is 80.
[0068] Table 2 Performance test results of titanium dioxide obtained in Example 2
[0069]
[0070] Comparative Example 1: Conventional salt treatment of metatitanic acid.
[0071] ZnO: 0.1~0.3%; KOH: 0.25~0.5%; H3PO4: 0.01~0.15%.
[0072] (1) Take a second wash material with a concentration of 300 g / L of titanic acid (calculated as TiO2) and a volume of 300 mL in a glass beaker, start stirring, add 2.25 g of 10% KOH by weight, and stir for 30 minutes; add 1.35 g of 10% phosphoric acid by weight (calculated as P2O5), stir for 30 minutes; add 0.18 g of zinc oxide powder, and stir for 1 hour.
[0073] (2) The treated slurry is filtered to form a filter cake, which is placed in an evaporating dish and dried at 150°C. The dried material is broken into pieces in the evaporating dish and calcined in a muffle furnace at 850°C for 1 hour. The rutile crystal content of the calcined sample is detected to be 99.1%. The color index of the sample is: L*: 98.70b*: 1.39.
[0074] (3) Take 80 g of the calcined sample, crush it with a universal grinder, add deionized water to make a slurry with a slurry concentration of 700 g / L, add 4 g of sodium hexametaphosphate with a weight concentration of 5% (calculated as P2O5), and grind at 9600 rpm for 1 hour.
[0075] (4) Prepare the sand-grinded slurry to a concentration of 300 g / L, raise the temperature to 95°C, add 13.3 g of sodium silicate solution with a weight percentage concentration of 12% (in terms of SiO2) through an axial flow pump, and add for 30 minutes. Use NaOH solution to control the slurry pH to 10.0 and stir for 30 minutes. Add acidifier dilute sulfuric acid through an axial flow pump at about 90 minutes until the pH value is 3.0, and the aging time is 1 hour.
[0076] (5) Cool the slurry to 60°C, add NaOH solution dropwise to make the slurry pH value 5.5, and add 23.9mL of aluminum sulfate with a concentration of 100.51g / L and NaOH solution in parallel, and control the pH value to 4.5-5.5. The addition time is 55 minutes. Mature for 1.5 hours. Wash, dry, and steam powder. The acid solubility of the test sample is 12.1%; the color index of the test sample is: L*: 98.81b*: 1.33, and the application performance is tested. The gloss at 20° is 68, and the gloss at 60° is 80.
[0077] Comparative Example 2: Aluminum titanate treatment.
[0078] Al2O3: 0.2-0.5% KOH: 0.25~0.5%; H3PO4: 0.01~0.15%.
[0079] (1) Take 300 g / L titanic acid (calculated as TiO2) and 300 mL of the second wash material in a glass beaker, start stirring, add 2.25 g of 10% KOH by weight, and stir for 30 minutes; add 1.35 g of 10% phosphoric acid by weight (calculated as P2O5), and stir for 30 minutes; add 2.69 mL of 100.51 g / L aluminum sulfate (calculated as Al2O3), and stir for 1 hour.
[0080] (2) The treated slurry is filtered to form a filter cake, which is placed in an evaporating dish and dried at 150°C. The dried material is broken into pieces in the evaporating dish and calcined in a muffle furnace at 850°C for 1 hour. The rutile crystal content of the calcined sample is detected to be 99.1%. The color index of the sample is: L*: 98.57b*: 1.51.
[0081] (3) Take 80 g of the calcined sample, crush it with a universal grinder, add deionized water to make a slurry with a slurry concentration of 700 g / L, add 4 g of sodium hexametaphosphate with a weight concentration of 5% (calculated as P2O5), and grind at 9600 rpm for 1 hour.
[0082] (4) Prepare the sand-grinded slurry to a concentration of 300 g / L, raise the temperature to 95°C, add 13.3 g of sodium silicate solution with a weight percentage concentration of 12% (in terms of SiO2) through an axial flow pump, and add for 30 minutes. Use NaOH solution to control the slurry pH to 10.0 and stir for 30 minutes. Add acidifier dilute sulfuric acid through an axial flow pump at about 90 minutes until the pH value is 3.0, and the aging time is 1 hour.
[0083] (5) Cool the slurry to 60°C, add NaOH solution dropwise to make the pH value of the slurry 5.5, and add 23.9mL of aluminum sulfate with a concentration of 100.51g / L and NaOH solution in parallel, and control the pH value to 4.5-5.5. The addition time is 55 minutes. Mature for 1.5 hours. Wash, dry, and steam powder. The acid solubility of the sample is 12.7%; the color index of the sample is L*: 98.61b*: 1.43, and the application performance is tested. The gloss at 20° is 65, and the gloss at 60° is 75.
[0084] Table 3 Performance test results of titanium dioxide obtained in Comparative Examples 1-2
[0085]
[0086] From the L value and b value of the calcined samples of Examples 1-2 and Comparative Examples 1 and 2 and the rutile conversion rate, the calcined samples of Examples 1 and 2 are significantly higher than those of Comparative Examples 1 and 2. The use of potassium phosphate zinc and aluminum salts in combination with metatitanic acid is better than the treatment of potassium, phosphorus zinc, and better than the treatment of potassium, phosphorus, and aluminum. Metatitanic acid is easy to sinter when treated with potassium phosphate zinc, which affects the L value and b value of titanium dioxide. Although titanium dioxide is not easy to sinter when treated with potassium phosphate aluminum salt, since aluminum salt is an inhibitor of rutile conversion, metatitanic acid needs to be calcined at a higher temperature to be converted into rutile titanium dioxide, which also affects the L value and b value of titanium dioxide. From the acid solubility rate of the coated samples of Examples 1 and 2 and Comparative Examples 1 and 2, it can be found that the first coated sample and the second coated sample of the embodiment are significantly lower than those of the comparative example. The lower the acid solubility rate, the stronger its ability to resist concentrated sulfuric acid and the higher its weather resistance.
[0087] From the acid solubility data of Examples 1 and 2, the first coated sample is higher than the calcined sample after coating, indicating that the secondary calcination dehydrates the hydrated SiO2 and hydrated Al2O3 of the coating to form a denser film layer, further reducing the surface hydroxyl content, reducing the surface voids of titanium dioxide, and improving the weather resistance of titanium dioxide.
[0088] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the embodiments made by those skilled in the art fall within the scope defined by the claims attached to the present invention.
Claims
1. A method for preparing super weather-resistant and high-gloss titanium dioxide, characterized in that The following steps are involved: S1, taking metatitanic acid and adding deionized water to make a slurry to obtain a metatitanic acid slurry, adding a salt treatment agent for reaction, wherein the salt treatment agent includes potassium salt, phosphorus salt, zinc salt and aluminum salt, wherein the amount of phosphorus salt added is 0.01-0.15% of the mass of TiO2 based on the mass of P2O5; the amount of zinc salt added is 5-10% of the mass of TiO2; the amount of potassium salt added is 0.25-0.45% of the mass of TiO2; and the amount of aluminum salt added is 0.05-0.2% of the mass of TiO2 based on the mass of Al2O3; S2, filtering, drying and calcining the slurry obtained in S1 to prepare a primary rutile titanium dioxide product; S3, crushing, pulping and sand-milling the primary rutile titanium dioxide obtained in S2; S4, making the surface of the titanium dioxide particles in the slurry prepared in S3 uniformly coated with hydrated SiO2; S5, making the surface of the slurry particles prepared in S4 evenly coated with a dense aluminum film, washing and drying; S6, calcining, cooling and crushing the material dried in S5.
2. The method for preparing the super weather-resistant and high-gloss titanium dioxide according to claim 1, characterized in that: In S3, the primary rutile titanium dioxide is made into a slurry with a concentration of 700-800 g / L, and sodium hexametaphosphate is added in an amount of 0.2-0.4% by mass of TiO2 based on the mass of P2O5, or sodium silicate is added in an amount of 0.2-0.4% by mass of TiO2 based on the mass of SiO2, and then sand-milled.
3. The method for preparing the super weather-resistant and high-gloss titanium dioxide according to claim 2, characterized in that: S4 includes the following steps: The sand-grinding slurry obtained in S3 is prepared into a slurry with a concentration of 200-400 g / L, and the temperature is raised to 75-95°C. Sodium silicate is added in an amount of 2-3% by mass of TiO2 in terms of SiO2, and the pH of the slurry is controlled to be 9.5-10.5 with stirring. An acidulant is added until the pH of the slurry reaches 3.0-4.0, and the slurry is matured; preferably, the acidulant is acetic acid or dilute sulfuric acid; more preferably, the acidulant is acetic acid.
4. The method for preparing super weather-resistant and high-gloss titanium dioxide according to claim 1, characterized in that: S5 includes the following steps: The slurry prepared by S4 is cooled to 55-65°C, the pH value is adjusted to 4.5-5.5, and aluminum sulfate or sodium aluminate is added at 2-5% of the mass of TiO2 based on Al2O3 to form a dense aluminum coating, and the mixture is aged for 1.5-2 hours.
5. The method for preparing super weather-resistant and high-gloss titanium dioxide according to claim 1, characterized in that: The process also includes S7, adding water to the titanium dioxide obtained in S6 to prepare a titanium dioxide slurry with a mass concentration of 200 to 400 g / L, adding aluminum sulfate or sodium aluminate with a TiO2 mass of 0.1 to 1% based on Al2O3, controlling the pH value to 8 to 9, and obtaining a boehmite-type aluminum coating; S8: washing, drying, adding all-purpose powder and steam powder to the coating material prepared in S7.
6. The method for preparing super weather-resistant and high-gloss titanium dioxide according to claim 1, characterized in that: The drying temperature in S2 is 150-200°C, and the calcination temperature is 820-870°C.
7. The method for preparing the super weather-resistant and high-gloss titanium dioxide according to claim 3, characterized in that: The addition time of acetic acid in S4 is 1.5 to 3 hours.
8. The method for preparing the super weather-resistant and high-gloss titanium dioxide according to claim 3, characterized in that: The aging time in S4 is 1 to 2 hours.
9. The method for preparing super weather-resistant and high-gloss titanium dioxide according to claim 1, characterized in that: The calcination temperature in S6 is 600-800°C, and the calcination time is 10-30 minutes.
10. Titanium dioxide prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
paper identification device
CN105118140B
A method for preparing high-whiteness, high-temperature-resistant masterbatch grade titanium dioxide
CN106118140B
Preparation method of anatase titanium dioxide with high weather resistance
CN112143261A
Cited By
Core-shell type conductive titanium dioxide and preparation method thereof
CN120164655A